2021
DOI: 10.1186/s12882-021-02592-8
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of intervention based on the transactional model on improving coping efforts and stress moderators in hemodialysis patients in Tehran: a randomized controlled trial

Abstract: Background Present study was conducted to determine the effect of training on coping efforts and stress moderators, based on transactional model of Lazarus and Folkman, in hemodialysis patients. Methods This is a randomized controlled clinical trial on 116 hemodialysis patients referred to dialysis centers in Tehran from May to August 2018. The patients were assigned to two experimental and control groups using a simple randomization method. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Meditation-guided make patient hemodialysis could improve quality of life with achievement confidence, clarity of mind, control of anger, feeling inspired to manage illness/ Resume routine work, reduction of laziness Ghaffari, MA, et al (2021) The effectiveness of an intervention based on the transactional model on improving coping efforts and stress moderators in hemodialysis patients in Tehran: a randomized controlled trial Based on results study show that the average patient aged hemodialysis over 50 years will have an influence on its physiology, so the patient will experience physiological function if not guarded (Suriyong et al, 2022). Based on the results study by Zainordin et al (2021a), in part, big patient hemodialysis manifold sex men (58%) and women (42%) as well skinned white (67%) and skinned black (33%) (Pike et al, 2020).…”
Section: Alireza Et Al (2019)mentioning
confidence: 99%
See 3 more Smart Citations
“…Meditation-guided make patient hemodialysis could improve quality of life with achievement confidence, clarity of mind, control of anger, feeling inspired to manage illness/ Resume routine work, reduction of laziness Ghaffari, MA, et al (2021) The effectiveness of an intervention based on the transactional model on improving coping efforts and stress moderators in hemodialysis patients in Tehran: a randomized controlled trial Based on results study show that the average patient aged hemodialysis over 50 years will have an influence on its physiology, so the patient will experience physiological function if not guarded (Suriyong et al, 2022). Based on the results study by Zainordin et al (2021a), in part, big patient hemodialysis manifold sex men (58%) and women (42%) as well skinned white (67%) and skinned black (33%) (Pike et al, 2020).…”
Section: Alireza Et Al (2019)mentioning
confidence: 99%
“…Kidneys also need to practice breathing, such as exercising deep breathing and progressive relaxation. Exercise breathing this proven could lower stress levels and regulate emotions in patients undergoing Hemodialysis (Ghaffari, Morowatisharifabad, et al, 2021).…”
Section: Alireza Et Al (2019)mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that patients on hemodialysis were dealing with many psychological tensions in addition to the problems related to treatment [ 5 ]. In dialysis treatment, patients receiving MHD deal with significant stresses due to the aggravation of chronic renal failure, and since the treatment of this disease is a long-term process, it affects the patients’ psychosocial function [ 6 , 7 ]. Many psychiatric disorders are seen in patients on MHD, such as stress, depression, and anxiety.…”
Section: Introductionmentioning
confidence: 99%